A Catalog of Local Universe Fast Radio Bursts from CHIME/FRB and the KKO - The CHIME/FRB Collaboration; Mandana Amiri; Daniel Amouyal; Bridget C. Andersen; Shion Andrew; Kevin Bandura; Mohit Bhardwaj; P. J. Boyle; Charanjot Brar; Alyssa Cassity; Shami Chatterjee; Alice P. Curtin; et al. (The Astrophysical Journal Supplement Series)
We present the first catalog of fast radio burst (FRB) host galaxies from CHIME/FRB Outriggers, selected uniformly in the radio and the optical by localizing 81 new bursts to 2″ × ∼ 60″ accuracy using CHIME and the k’niʔatn k’l ⌣ stk’masqt Outrigger station, located 66 km from CHIME. Of the 81 localized bursts, we use the probabilistic association of transients to their hosts algorithm to securely identify 21 new FRB host galaxies, and compile spectroscopic redshifts for 19 systems, 15 of which are newly obtained via spectroscopic observations. The most nearby source is FRB 20231229A, at a distance of 90 Mpc. One burst in our sample is from a previously reported repeating source in a galaxy merger (FRB 20190303A). Three new FRB host galaxies (FRBs 20230203A, 20230703A, and 20231206A) are found toward X-ray and optically selected galaxy clusters, potentially doubling the sample of known galaxy cluster FRBs. A search for radio counterparts reveals that FRB 20231128A is associated with a luminous persistent radio source (PRS) candidate with high significance ( P _cc  ∼ 10 ^−2 ). If its compactness is confirmed, it would be the nearest known compact PRS at z = 0.1079. Our catalog significantly increases the statistics of the Macquart relation at low redshifts ( z  < 0.2). In the near future, the completed CHIME/FRB Outriggers array will produce hundreds of FRBs localized with very long baseline interferometry (VLBI). This will significantly expand the known sample and pave the way for future telescopes relying on VLBI for FRB localization.